2020
DOI: 10.1007/s00705-020-04808-y
|View full text |Cite
|
Sign up to set email alerts
|

Fecal, oral, blood and skin virome of laboratory rabbits

Abstract: Here, we investigated the fecal, oral, blood, and skin virome of 10 laboratory rabbits using a viral metagenomic method. In the oral samples, we detected a novel polyomavirus (RabPyV), and phylogenetic analysis based on the large T antigen, VP1 and VP2 regions indicated that the novel strain might have undergone a recombination event. Recombination analysis based on related genomes confirmed that RabPyV is a multiple recombinant between rodent-like and avian-like polyomaviruses. In fecal samples, three partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Two PBV contigs were obtained and PCR-confirmed from two fecal pools, with lengths of 1685/1684 bp. The distributions of these sequences were coincident with other PBVs, which have been detected in the feces of human, rabbit, dog, pig, rat, and bird 5,41 . Further analyses of these two segments revealed 2 RdRp region of PBV.…”
Section: Characteristics Of Selected Zoonotic Viruses By Characterizi...mentioning
confidence: 52%
See 1 more Smart Citation
“…Two PBV contigs were obtained and PCR-confirmed from two fecal pools, with lengths of 1685/1684 bp. The distributions of these sequences were coincident with other PBVs, which have been detected in the feces of human, rabbit, dog, pig, rat, and bird 5,41 . Further analyses of these two segments revealed 2 RdRp region of PBV.…”
Section: Characteristics Of Selected Zoonotic Viruses By Characterizi...mentioning
confidence: 52%
“…PBV is small, nonenveloped viruses with a segmented linear dsRNA genome, segments size ranges from 1.7 to 2.5 kb. In which, the large segment encodes a capsid preceursor, while the small one encodes the viral RNA-dependent RNA polymerase (RdRp) 5 . PBVs have been detected in the feces of many different hosts, including humans, rabbits, dogs, pigs, rats, and birds 5,41 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study also confirmed the distinction in virome composition between the large and the small intestine in rhesus monkey and pigs with a higher phage diversity in the lumen and predominance of eukaryotic viruses predominate in mucosal samples [40]. Recently, the faecal, oral, blood, and skin virome of laboratory rabbits were described leading to the identification of a novel polyomavirus [41].…”
Section: Non Mouse Modelsmentioning
confidence: 68%
“…144,145 Recently, rabbits have been used, leading to the identification of a novel polyomavirus. 146 Finally, swine models have also been used for virome in fecal virome transplants, which have been shown to act against necrotizing enterocolitis in pigs. 147…”
Section: Challenges and Limitationsmentioning
confidence: 99%